Department heads negotiating emerging managerialism: The Central Eastern European context. (September 2019) - Machovcová, Kateřina; Zábrodská, Kateřina; Mudrák, Jiří
The Czech higher educational system has transformed over the past three decades from a state-centred model evolving via strong academic autonomy to the current system, which is characterised by academic freedom but also heightened pressure to produce measurable research output. The purpose of this study was to explore how Czech academic middle managers relate to this emerging managerialism in their faculties. We conducted 31 interviews with Heads of Departments (HoDs) and, using thematic analysis, we identified three central themes. First, despite their enhanced managerial tasks, the HoDs strongly identified themselves as researchers. Second, the HoDs instrumentally adopted certain managerialist practices congruent with their values as academic professionals with a primary focus on increasing research performance and the ability to acquire additional financing through grants. Third, the HoDs used practices to lessen the negative effects of managerialist pressures, such as diverting the administrative overload from academics. In conclusion, academic middle managers supported performance management even though existing structural differences benefited certain departments more than others. Paradoxically, the HoDs more likely to succeed in the quantitative assessment appeared to be in a better position to buffer some of the negative impacts of the managerialist reforms.